2012
DOI: 10.3168/jds.2011-4972
|View full text |Cite
|
Sign up to set email alerts
|

A daily herd Markov-chain model to study the reproductive and economic impact of reproductive programs combining timed artificial insemination and estrus detection

Abstract: Our objective was to compare the economic and reproductive performance of programs combining timed artificial insemination (TAI) and different levels of AI after estrus detection (ED) using a daily Markov-chain model. A dairy herd was modeled with every cow following daily probabilistic events of aging, replacement, mortality, pregnancy, pregnancy loss, and calving. The probability of pregnancy depended on the combination of probability of insemination and conception rate (CR). All nonpregnant cows had a proba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
130
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 95 publications
(139 citation statements)
references
References 39 publications
8
130
0
1
Order By: Relevance
“…These factors seem to be the most important determinants of economic reproductive efficiency (Giordano et al, 2012;Galvao et al, 2013). However, the overall value of improving reproductive efficiency is a combination of all economic factors interacting with no single factor being defined as the most important in all situations.…”
Section: The Economic Value Of Improving Reproductive Performancementioning
confidence: 99%
See 4 more Smart Citations
“…These factors seem to be the most important determinants of economic reproductive efficiency (Giordano et al, 2012;Galvao et al, 2013). However, the overall value of improving reproductive efficiency is a combination of all economic factors interacting with no single factor being defined as the most important in all situations.…”
Section: The Economic Value Of Improving Reproductive Performancementioning
confidence: 99%
“…Milk productivity, milk sales and milk income over feed cost As milk productivity increases, feed costs also increase and although some studies found that the milk income over feed cost increased with reproductive performance (Giordano et al, 2012;Kalantari and Cabrera, 2012), other studies reported that the milk income over feed cost could, at times, decrease slightly as reproductive performance increases (Cabrera, 2012;Galvao et al, 2013). The relationship between milk production and feed consumption is complex and interacts with many factors such as the herd structure, feeds prices and the shape and persistence of lactation curves.…”
Section: The Economic Value Of Improving Reproductive Performancementioning
confidence: 99%
See 3 more Smart Citations